Asia‐Pacific mussel watch: Monitoring of butyltin contamination in coastal waters of Asian developing countries - Sudaryanto, Agus; Takahashi, Shin; Monirith, In; Ismail, Ahmad (Society of Environmental Toxicology and Chemistry, 2002)
Butyltin compounds (BTs) including mono-, di-, and tributyltin and total tin (ΣSn), were determined in green mussels (Perna viridis) from various Asian developing countries, such as Cambodia, China (Hong Kong and southern China), Malaysia, India, Indonesia, the Philippines, and Vietnam, to elucidate the contamination status, distribution, and possible sources and to assess the risks on aquatic organisms and humans. Butyltin compounds were detected in green mussels collected from all the sampling location investigated, suggesting widespread contamination of BTs along the coastal waters of Asian developing countries. Among butyltin derivatives, tributyltin (TBT) was the predominant compound, indicating its ongoing usage and recent exposures in Asian coastal waters. Higher concentrations of BTs were found in mussels collected at locations with intensive maritime activities, implying that the usage of TBT as a biocide in antifouling paints was a major source of BTs. In addition, relatively high concentrations of BTs were observed in mussels from aquaculture areas in Hong Kong and Malaysia, as it has been reported in Thailand. With the recent improvement in economic status in Asia, it is probable that an increase in TBT usage will occur in aquaculture. Although contamination levels were generally low in mussel samples from most of the Asian developing countries, some of those from polluted areas in Hong Kong, India, Malaysia, the Philippines, and Thailand revealed levels comparable to those in developed nations. Furthermore, the concentrations of TBT in some mussels from polluted areas exceeded the threshold for toxic effects on organisms and estimated tolerable average residue levels as seafoods for human consumption. A significant correlation was observed between the concentrations of ΣBTs and ΣSn in mussels, and ΣBTs were made up mostly 100% of ΣSn in mussels taken from locations having intensive maritime/human activities. This suggests that anthropogenic BTs represent the major source of tin accumulation in mussels. To our knowledge, this is a first comprehensive report on butyltin pollution monitoring in developing countries in the Asia-Pacific region.